Comparative morphological study of peripheral blood cells in tow species of true lizards family Lacertidae - ابراهيم, نهلة; المصري, عروب; مهنا, حسان (Latakia University Journal -Biological Sciences Series, 2022)
This present study aimed to compare between two species of lizards Phoenicolacerta laevis and Ophisops elegans that belong to the true lizards family Lacertidae, by studying the morphology of peripheral blood cells (red blood cells - white blood cells - platelets) by making blood smears and coloring them with a Wright stain. The results showed that there were noticeable differences between the blood smears of each species, where the values measurements were greater in phoenicolacerta laevis in addition to the absence of neutrophils in it. The difference also appeared between the smears of the same species in different sampling areas.